ANALISIS PENERAPAN METODE PENYUSUTAN ASET TETAP DAN PENGARUHNYA TERHADAP LABA PADA PT. KLASAMAN INDAH RAYA KOTA SORONG - Jitmau, Fanny; Pangkereg, cristian; Purba, Ruth Eiriva Amanda (Jurnal Pitis AKP, 2021)
The purpose of this study is to ascertain the impact of the depreciation technique on the firm earnings at PT. Klasaman Indah Raya Sorong City. In Sorong City's Jalan Gurami, this study is situated. This shipping business offers ship repair or ship repair services. According to the research conducted at PT. Klasaman Indah Raya Sorong City g, a strategic research approach was adopted to gather pertinent data and research objects. Researchers employ three research techniques: interviewing, observing, and documenting. PT. Klasaman Indah Raya Kota Sorong uses the straight-line depreciation technique to calculate the value of its fixed assets, according to the study's findings. The amount of depreciation expense is less when utilizing the straight-line technique than when using the double-declining balance method. The amount of depreciation is less when using the straight-line approach than when using the year number method, which is smaller when compared to the amount of depreciation when using the double-declining and straight-line metho